Comparison of basic motor skills and physical fitness between (pre-)pubertal children from parkour and team sports - Chris Konushevci; Joel Mason; Konstantin Warneke; Astrid Zech (Frontiers in Sports and Active Living)
BackgroundParkour is a modern sport known for daring jumps and moves in urban environments that require exceptional motor skills and various sports-specific techniques. Although it is increasingly popular among children and adolescents, training routines in youth Parkour are still rather driven by personal beliefs and experience of coaches than by evidence.PurposeThis study aims to analyze basic motor skills and physical fitness of youth Parkour athletes compared to team sports athletes.Study designCross-sectional study with matched-pair analysis.MethodsSeventeen youth Parkour (12.50 ± 1.80 years) and seventeen team sports athletes (11.90 ± 1.70 years), matched for height and weight, participated in this study. Tests included static (single-leg postural sway = PS) and dynamic balance (Y-Balance test = YBT), jumping (countermovement jump = CMJ, drop jump = DJ, side-hop = SH), muscle strength (planks, pull-ups = PU) and basic gymnastics skills (bridging = BG, handstand = HS, cartwheel = CW).ResultsThe Parkour group performed significantly better in the CMJ (p = 0.014), the anterior direction of the YBT (p < 0.001), cartwheel performance (p = 0.019), and pull-ups (p = 0.029) when compared to the team-sports group. Moderate but non-significant differences were observed in PS for the dominant (p = 0.12) and non-dominant leg (p = 0.14) as well as in SH (p = 0.06). No further significant differences were observed.ConclusionChildren practicing Parkour demonstrated superior performances in certain parameters of motor skills and physical fitness compared to team sports athletes. The findings suggest that Parkour may contribute positively to children's overall physical development. However, more intervention studies with a prospective study design are needed for further recommendations.